Elevation of plasma podoplanin in Kawasaki disease - Xu, Ling; Li, Wei; Geng, Zhimin; Peng, Zhaoyang; Sun, Anna; Qin, Wenjun; Xie, Chunhong; Gong, Fangqi; Shen, Hongqiang (Journal of laboratory medicine, 2025)
Kawasaki disease (KD) is a systemic vasculitis that results in abnormalities in the coronary arteries. Podoplanin (PDPN) and its receptor C-type lectin-like receptor 2 (CLEC-2) are involved in inflammatory hemostasis and have also been proved to be effective predictive markers for early evaluation of sepsis and coagulation. This study aimed to investigate the expression of PDPN and its receptor CLEC-2 in the patients with KD, and evaluate the relationship between PDPN and clinical laboratory parameters.